The Role of the Managerial Function of Supervisor Model 4S towards Patient Safety Culture at Sawahlunto General Hospital - Annedya Handayani; Yulastri Arif; Zifriyanthi Minanda Putri (HM Publisher, 2022)
Background: The culture of patient safety in hospitals is still not well implemented. Maintaining a patient safety culture is the responsibility of every healthcare professional. This study aims to explore the relationship between the supervisory function of the 4S model and the culture of patient safety at Sawahlunto General Hospital. Methods: This study is an observational study. A total of 52 respondents participated in this study. This study uses a questionnaire instrument to assess the role of supervisory and managerial functions in the 4S model with patient safety culture. Data analysis was performed by SEM-PLS. Results: There is a significant relationship between the characteristics of nurses and patient safety culture at Sawahlunto General Hospital. There is a significant relationship between the characteristics of supervisors and interpersonal supervisors with the managerial function of supervisors at Sawahlunto General Hospital. Conclusion: The managerial function of the Model 4S supervisor is related to the patient safety culture at Sawahlunto General Hospital.